ADE494 : Curatorship / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course aims to introduce students with basic principles, approaches and strategies in art curatorship. Considering art and design curatorship as a creative practice, this course will also discuss curatorship in relation to artists, public spaces, museums, galleries, larger urban settings, physical and virtual spaces. At the end of the course, students should be able to understand basic principles, approaches and strategies in art curatorship and write a curatorial essay on a chosen theme for an art exhibition.